2016
DOI: 10.1007/s11440-016-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of rock joint frictional strength in the containment of fracture propagation

Abstract: The fracturing phenomenon within the reservoir environment is a complex process that is controlled by several factors and may occur either naturally or by artificial drivers. Even when deliberately induced, the fracturing behaviour is greatly influenced by the subsurface architecture and existing features. The presence of discontinuities such as joints, artificial and naturally occurring faults and interfaces between rock layers and microfractures plays an important role in the fracturing process and has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…The risk of earthquakes triggered by hydraulic fractures is closely related to the stress state of rock strata and the development of fractures . It determines whether to initiate new tensile fractures or the propagation of preexisting fractures dominates the failure . Wang and Li et al found that hydraulic fractures interacted with random microfractures will make the complex geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of earthquakes triggered by hydraulic fractures is closely related to the stress state of rock strata and the development of fractures . It determines whether to initiate new tensile fractures or the propagation of preexisting fractures dominates the failure . Wang and Li et al found that hydraulic fractures interacted with random microfractures will make the complex geometry.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 It determines whether to initiate new tensile fractures or the propagation of preexisting fractures dominates the failure. 8,22,[40][41][42][43] Wang and Li et al 38 found that hydraulic fractures interacted with random microfractures will make the complex geometry. Li et al 42 investigated the hydraulic fracturing process of granite with different orientations of two precut flaws by analyzing the acoustic emissions data.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on various parameters, (1) the hydraulic fracture can cross the natural fracture, (2) it can be stopped by the natural fracture, or (3) it hydraulically activates the natural fracture. Microseismic imaging of hydromechanical reactivation of fractures is a useful tool to assess fracture geometry, i.e., the fracture height, length, orientation [40], frictional properties [23], and fractures interaction [47,54,56]. However, the interpretation of the induced microseismicity is not straightforward since pore pressure perturbations can promote both seismic and aseismic motions [14] with the induced slip not necessarily being the source of instability [35].…”
Section: Introductionmentioning
confidence: 99%
“…A rising tide of evidence from practical treatment in the field implies that hydrofracturing cracks may initiate and grow in a complicated way that is highly affected by the complexity of in‐situ stresses and the heterogeneity of reservoir formations . Some factors play critical roles in the optimisation and evaluation of hydraulic fracturing stimulation, namely, crack types (tensile or shear), the reasons for crack nucleation, propagation, and coalescence in deep reservoirs, the effects of heterogeneous gravels, and in‐situ stresses . It is known that the initiation and growth behaviours of hydrofracturing cracks are strongly influenced by the heterogeneity of reservoir rocks such as glutenite that is found extensively in tight gas reservoirs .…”
Section: Introductionmentioning
confidence: 99%